(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To examine structure-function correlations and their temporal dynamics in patients with progressive primary open-angle glaucoma (POAG) versus stable POAG based on optical coherence tomography (OCT) and static automated perimetry. Material and Methods: We examined and followed up 193 patients (338 eyes). Of 338 eyes with glaucoma, 64 had preperimetric glaucoma and 274 had perimetric glaucoma. Patients were followed up for an average of 70.6 months. Dynamics of structure-function correlations was analyzed in 248 eyes. Each study eye was assessed as to whether the disease course was progressive or stable based on mean deviation (MD) dynamics over the follow-up. Results: At baseline, in a total sample of patients with POAG, there was a moderate positive correlation between MD and most examined structural parameters (average thicknesses in the retinal nerve fiber layer [RNFL], inferior RNFL, 7/5 clock hour sector, and macular nerve fiber layer [mNFL]). MD was positively weakly correlated with ganglion cell complex (GCC) thickness (r = 0.2834, p < 0.05). MD was positively moderately correlated with GCC thickness (r = 0.3976, p < 0.05) in eyes with stable POAG, and positively weakly correlated with it (r = 0.2506, p < 0.05) in eyes with progressive POAG. Additionally, mNFL thickness was positively strongly correlated with GCC thickness (r = 0.7069, p < 0.05) in eyes with stable POAG, and positively moderately correlated with it (r = 0.6235, p < 0.05) in eyes with progressive POAG. In progressive POAG, a positive correlation between MD and GCC thickness changed from weak (r = 0.277, p < 0.05) to moderate (r = 0.4136, p < 0.05), whereas a positive correlation between mNFL thickness and GCC thickness changed from moderate (r = 0.6242, p < 0.05) to strong (r = 0.7056, p < 0.05) over the follow-up period. In stable POAG, MD was positively moderately correlated with GCC thickness at baseline (r = 0.3655, p < 0.05), and was not correlated over the follow-up (p > 0.05). Conclusion: At baseline, in a total sample of eyes with POAG, there was a positive correlation between MD and structural OCT-based parameters, with the strongest correlation (moderate correlation between MD and GCC thickness [r = 0.4989, p < 0.05] and between MD and mNFL thickness [r = 0.3905, p < 0.05]) found in eyes with stage 2 POAG. Stronger positive structure-function correlations were found in eyes with stable glaucoma (e.g., a moderate correlation between MD and GCC thickness [r = 0.3976, p < 0.05] and a strong correlation between mNFL thickness and GCC [r = 0.7069, p < 0.05]) compared to eyes with progressive glaucoma (a weak correlation between MD and GCC thickness [r = 0.2506, p < 0.05]) and a moderate correlation between mNFL and GCC thickness [r = 0.6325, p < 0.05]). The strength of structure-function correlation increased over the follow-up period in eyes with progressive glaucoma, and decreased over the follow-up period in eyes with stable glaucoma. In progressive POAG, a positive correlation between MD and GCC thickness changed from weak (r = 0.277, p < 0.05) to moderate (r = 0.4136, p < 0.05), whereas in stable POAG, MD was positively moderately correlated with GCC thickness at baseline (r = 0.3655, p < 0.05), and did not correlate with it at the final follow-up (p > 0.05).